Antimicrobial Activity of Ga-Doped Hydroxyapatite Nanostructures: Synthesis, Morphological, Spectroscopic, and Dielectric Properties - Albulym, Obaid; Kaygili, Omer; Hussien, Mai S. A.; Zahran, H. Y.; Kilany, Mona; Yahia, I. S.; El-Kott, Attalla Farag (Amer Scientific Publishers, 2019)
In the present paper, seven samples of hydroxyapatite (HAp) nanoparticles doped with different amounts (e.g., 0%, 1%, 3%, 6%, 9%, 12%, and 15% [wt.]) of Ga-ions were synthesized at low temperature using the microwave-assisted sol-gel technique. FT-Raman/Fourier-transform infrared (FTIR) technique, X-ray diffraction (XRD), dielectric/alternating current conductivity measurements, scanning electron microscopy, and antimicrobial tests were utilized in order to characterize the synthesized samples. The Ga content was observed to affect the crystallite size as well as the crystallinity of HAp. Variations were observed in the lattice parameters, lattice strain, and dislocation density. FTIR analysis revealed that HAp structure possessed the carbonate group. Thus all samples have promising medical applications, as this group improves the bioactivity of HAp. Dielectric properties, as well as the alternating current electrical conductivity, were also observed to be affected by the Ga content. Furthermore, the present study demonstrated that the Ga-doped HAp nanostructures exerted a considerable inhibitory effect on bacteria (Pseudomonas aeruginosa, Staphylococcus aureus, and Escherichia coli) and fungi (Candida albicans). Therefore, the Ga-doped HAp nanostructures are proposed as a promising candidate for applications in the field of bone cement engineering.
Keywords: Ga-Doped Hydroxyapatite; Microwave-Assisted Sol-Gel Technique; FTIR/Raman Spectroscopy; Dielectric Properties; Antimicrobial Activity